Penerapan Model Pembelajaran Kontekstual Terhadap Hasil Belajar Fisika - Sasmita, Petri Reni; Sahida, Desrianti; Mawati, Relis (Jurnal Ilmiah Pendidik Indonesia, 2022)
This research is motivated by several problems that occur in learning, so that student learning outcomes have not reached the KKM that has been set. This study aims to improve physics learning outcomes through the application of the Odd semester contextual learning model for the 2022/2023 academic year. This research is classroom action research which is conducted in two cycles. Each cycle consists of four stages, namely planning, implementation, observation, and reflection. The research subjects were students of class XI, totaling 25 students. Collecting data in this study using test questions. The results showed that the average learning outcomes of Physics in the first cycle were 40% categorized as poor and in the second cycle increased to 80% in the good category. Thus, it can be concluded that the application of the contextual learning model can improve physics learning outcomes for students in class XI for the academic year 2022/2023.